Investigating multilingualism and its association with executive functioning: An exploratory study comparing bilingual, trilingual and quadrilingual college students in India - Rajan, Garima; Patil, Nyanada (Lesya Ukrainka Eastern European National University, 2023)
Multilingualism has both advantages and disadvantages. Past research has highlighted this dichotomy by exploring the impact of linguistic ability on individuals’ executive functioning. This study explores the relationship between individuals’ linguistic ability (number of languages spoken) and their executive functioning, specifically, working memory – measured using the Corsi Block-Tapping task (Mueller, 2011a), inhibitory control – measured using the Go/No-Go task (Mueller, 2011b) and problem solving – measured using the Tower of London task (Mueller, 2011c) among bilingual, trilingual and quadrilingual Indian colleges students. Results from a Kruskal Wallis test indicated non-significant results for problem solving among the three groups. However, significant differences were found between groups for working memory (p = 0.050) (particularly between bilinguals and quadrilinguals, and trilinguals and quadrilinguals) and inhibitory control (p = 0.020) (particularly between trilinguals and quadrilinguals). The mixed results indicate a need for further research in this domain within the vast and diverse population of India.
Keywords: bilingualism; trilingualism; quadrilingualism; working memory; inhibitory control; problem solving; Indian population